PRAKTIK PENGGUNAAN INSEKTISIDA RUMAH TANGGA DI AREA BUFFER PELABUHAN TANJUNG EMAS WILAYAH KERJA KANTOR KESEHATAN PELABUHAN KELAS II SEMARANG - Ramadani Sukaningtyas; Ari Udijono; Martini Martini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Chemical control in the Semarang Tanjung Emas Port buffer area using insecticides from year to year is still an alternative in the Dengue Hemorrhagic Fever (DBD) disease control program by the Semarang Class II Port Health Office. In addition to the use of insecticides by program managers, there are also uses of insecticides which are often used by many households. The behavior of using household insecticides with inappropriate dosages and methods for a long time has the potential to cause Aedes aegypti vector resistance, thereby reducing the effectiveness of insecticides. This type of research is a descriptive observational study to identify the description of the behavior of the use of household insecticides in the buffer zone of the Port of Tanjung Emas Semarang. Interviews were conducted to find out the history of the use of insecticides. Respondents in this study were heads of households within a 400 meter radius of the Harbor fence. The results showed that most people use household insecticides at 93,85%. The most widely used type of insecticide is 83,08% topical application with DEET (diethyltoluamide) active ingredient. Most people have been using household insecticide for a long time, which is less than 15 years with the highest application time at night, 86,89%.